Standarisasi Dan Tipologi Pondok Pesantren Di Kota Samarinda - Khojir Khojir; Khairy Abusyairi (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2013)
This study belongs to qualitative study focusing on the standardization and typology of boarding schools. The technique of collecting the data used interview, observation, and documentation. The data were analyzed using descriptive qualitative covering data display, data reduction, and conclusion drawing. The research finding shows that boarding schools that meet implementation standard are Sabilal-Rasyad, Nabil Husin, al-Husna, Syaichona Cholil, Al-Istiqomah, Al-Rahmah, Asa’diyah, and al-Mujahidin. Meanwhile, the boarding schools that have not met yet the implementation standard are Al-Muna, Najwatul Ula, Hidayatul Mubtadiin, Al-Ittihad, and As-Suniyah. The category of type A covers the boarding schools of Nurul Iman, Al-Aziziyah, and Ar-Rahmah. The category of type B includes the boarding schools of Sabilal Rasyad, Darul Ihsan, MIC Technology, Syaikhona Cholil, Asa’diyah, Ihya’ Ulumuddin, and An-Nur. There is no boarding school in the city of Samarinda that includes in the category of type C. This research implies that the boarding schools that have not met the implementation standard should intensify the management.